A European perspective on public debt - Winfried Horstmann (Intereconomics, 1994)
Public debt in Europe has risen continuously over the last two decades. How is the transition to European Economic and Monetary Union, with the increasing economic interdependence between individual member states which it involves, likely to affect this situation? Which policy issues are of particular relevance in this setting?
Keywords: 330; Integration